Binging with Babish : 100 recipes recreated from your favorite movies and TV shows - Rea, Andrew (Houghton Mifflin Harcourt Publishing Company, 2019)
"Recipes recreated from beloved movies and TV shows by the host of one of the most popular food programs on the Internet"--